A century of inquiry in industrial safety: Intellectual genealogy and future prospects in unsafe behavior research - Sun, Ninghao; Tong, Ruipeng (Safety science, 2025)
•The theoretical mechanisms, industrial applications, and intervention strategies of unsafe behaviors are reviewed.•Applications in mining and construction have produced novel advances providing reference for cross-industry research.•The intervention strategy emphasizes behavioral risk assessment and the development of innovative safety training methods.•Individual behavioral portraits, risk prediction, and cross-scenario knowledge transfer need to be addressed in the future. Unsafe behavior is a primary cause of industrial accidents. However, the field is multifaceted with a complex knowledge system. Even if there are some relevant reviews, they mostly focus on individual cognition, specific industries, or technical tools like computer vision, lacking systematic integration of research topics, paradigms, and methods. Accordingly, this study systematically reviews the literature on unsafe behaviors in the industrial production. Using typology and bibliometric analysis, the study conducts descriptive statistics and academic characteristics analysis, completely describing the knowledge subjects, hot topics, and research gaps. The results are as follows: 1) The primary theoretical foundation is behavioral mechanism, with increased focus on the critical role that individual cognition plays. 2) The application research conducted in the mining and construction industries has, to some extent, produced novel advances in the subfields of identification, simulation, and propagation of unsafe behaviors. 3) The intervention strategy emphasizes behavioral risk assessment and the development of innovative safety training methods. 4) Individual behavioral portraits, risk prediction in advance, and cross-scene knowledge transfer are the three fields that future study should concentrate on. The study reveals the logic and core challenges of the current theory construction, industry application, and intervention path, points out the direction for future development, and makes specific suggestions. Particularly, in order to improve theory innovation and practice, it is important to deepen discipline integration, develop the ontology knowledge system and multimodal database, and strengthen collaboration among researchers, managers, and policymakers. This study would be a historical reference for future research.